Optimization of Cross-Linked Cassava Starch Coating Formulation by Response Surface Methodology and Its Preservation Effects on ‘Shatangju’ Mandarin - Chunli Deng; Oksana Melnyk; Guanli Li; Xiaochun Li; Yanghe Luo (Polish Journal of Food and Nutrition Sciences)
In this study, cassava starch cross-linked using sodium trimetaphosphate was used as basic material to prepare the preservation coating agent. The addition levels of β-cyclodextrin, phytic acid and glycerol were optimized by response surface methodology with the comprehensive index of oil permeability (OP) and the water vapor permeability (WVP) of starch-based coating. The optimal formulation of the cross-linked cassava starch-based coating was as follows: 3 g/100 g cassava cross-linked starch, 0.7 g/100 g β-cyclodextrin, 0.5 g/100 g phytic acid, and 0.5 g/100 g glycerol. The preservation coating solution prepared by the optimized formula was applied to the postharvest storage of ‘Shatangju’ mandarins. The coating treatment effectively slowed down the decline of firmness during storage for 20 days at room temperature, reduced the decay rate (by 111.73%) and weight loss rate (by 43.40%), and inhibited the postharvest respiration (by 42.06%) of fruit. The soluble solid content, titratable acidity and ascorbic acid content of the coated ‘Shatangju’ mandarins were higher 1.32 times, 1.55 times, and 1.52 times, respectively, compared with the corresponding indexes of the control fruits. All these results indicate that the coating treatment could effectively reduce the loss of nutrients, delay the wilting and decay, prolong the shelf life after harvest, and improve the commercial value of ‘Shatangju’ mandarins.